El Dorado [videorecording (DVD)] - Wayne, John, 1907-1979; Mitchum, Robert; Caan, James; Holt, Charlene, 1928-1996; Hawks, Howard, 1896-1977; Brown, Harry, 1917-1986 (John Wayne collection., 2005)
A sheriff fights cattlemen and empire builders as he tries to tame the West.